"I know English": Self-assessment of foreign language reading and writing abilities among young Chinese learners of English. (February 2019) - Liu, Huan; Brantmeier, Cindy
Abstract: A growing number of studies have examined self-assessment (SA) of language abilities; however, SA has not been investigated extensively in the context of language teaching and learning in China. This study aims to explore SA of reading and writing abilities among young Chinese learners of English, and the relationship between SA and objective tests of reading and writing. 106 Chinese learners of English (ages 12 to 14) completed a Reading Comprehension Test (captured by Free Recall, Sentence Completion, and Multiple-Choice Questions), a Writing Task (a picture-based writing prompt), and criterion-referenced SA Items. Correlational analyses revealed a significant correlation between scores of SA reading and reading comprehension. The correlation between scores of SA writing and writing production was also found to be significant. Findings indicate that young learners tend to self-assess their foreign language reading and writing abilities accurately. Findings add some empirical information useful for a better understanding of the trajectories of SA with young learners. Young learners' self-perceived strengths and weaknesses in reading and writing abilities are presented. The potential to use SA as a tool to promote foreign language instruction for young learners is explored.